A foaming injection molding wave absorbing material and its preparation method and application

By using absorbing materials with components such as polyetherimide and combined with supercritical state fluid foaming injection molding technology, the problem of existing absorbing materials being poorly performed in high-power environments is solved, and the excellent mechanical properties of the materials are achieved and wave absorption performance, suitable for high-power electromagnetic wave dark chambers.

CN118725569BActive Publication Date: 2025-02-18ZHUHAI LUBAN INTELLIGENT MFG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410975187.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-02-18
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

Existing wave-absorbing materials perform poorly in high-power electromagnetic wave environments, the material structure may fail at high power, and the flame retardant performance and wave-absorbing performance are also insufficient, making it difficult to meet the needs of high-power electromagnetic wave dark chambers.

Method used

Using absorbing materials with components such as polyetherimide, conductive fillers, zinc oxide and glycidyl methacrylate, the preparation of excellent mechanical properties and absorbing is achieved through heating and kneading and supercritical state fluid foaming injection molding technology. Materials of performance.

Benefits of technology

This absorbent material has good absorption effect in the 14KHZ-30MHZ frequency band and shows better absorption effect in the 30MHz-70GHz frequency band range. It also has high flame retardant, high temperature resistance and good mechanical properties, and is suitable for high power electromagnetic waves. darkroom.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004954319460000121
    Figure BDA0004954319460000121
  • Figure BDA0004954319460000122
    Figure BDA0004954319460000122
  • Figure BDA0004954319460000131
    Figure BDA0004954319460000131
Patent Text Reader

Abstract

The present invention discloses a foaming injection molding absorbing material and a preparation method and application thereof. It relates to the technical field of absorbing materials. The raw materials of the above-mentioned absorbing material include the following components: polyetherimide; conductive filler; zinc oxide; glycidyl methacrylate. The absorbing material of the present invention has a good absorption effect in the 14KHZ-30MHZ frequency band and a better absorption effect in the 30MHz-70GHz frequency band. In addition, it also has the characteristics of high flame retardancy, high temperature resistance, good mechanical properties, etc., and is a very suitable absorbing material for use in an electromagnetic darkroom. The absorbing material of the present invention can break through the pain points of the extremely poor absorption performance and extremely poor flame retardancy of the rigid foam absorbing material on the market below 30MHZ, and is also more suitable for harsh environments such as high temperature for high-power electromagnetic wave absorption, and is more cost-effective than any high-power absorbing material (such as honeycomb aramid) currently on the market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of absorbing materials, and in particular to a foaming injection molding absorbing material and a preparation method and application thereof. Background Art

[0002] Absorbers are a class of materials designed specifically to absorb electromagnetic wave energy. In an anechoic chamber, these materials play a vital role by reducing or eliminating the reflection and propagation of electromagnetic waves, minimizing electromagnetic interference in the test environment, thereby ensuring the accuracy and repeatability of test results. However, for high-power (below 35KW) anechoic chambers, existing absorbing materials face multiple technical challenges and limitations.

[0003] First, existing absorbing materials are usually designed for low-power environments, and their material structure and composition may fail or be damaged when facing high-power electromagnetic waves. High-power electromagnetic wave fields have more stringent requirements on the thermal, electrical, and mechanical properties of materials, and the tensile strength, fracture strain, and impact strength of existing materials often cannot meet the long-term stability requirements, resulting in poor performance or even failure in high-power environments.

[0004] Secondly, there are also certain problems with the flame retardancy and wave absorption performance of existing absorbing materials. In the application scenario of electromagnetic wave darkroom, these materials must have good heat resistance and flame retardancy to avoid fire or thermal runaway in high-power electromagnetic wave fields, thereby affecting the safety and stability of the test environment. At the same time, the stability of wave absorption performance and the performance attenuation after long-term use are also one of the technical problems that need to be solved at present.

[0005] Based on this, it is urgent to develop a new type of absorbing material to solve the above problems. Summary of the invention

[0006] The object of the present invention is to provide an absorbing material which can still exhibit excellent mechanical properties and absorbing properties in a high power environment.

[0007] The first aspect of the present invention is:

[0008] Provided is a wave absorbing material.

[0009] A second aspect of the present invention is:

[0010] Provided is a method for preparing a wave absorbing material.

[0011] The third aspect of the present invention is:

[0012] Application of the absorbing material.

[0013] Specifically, the technical solution adopted according to the first aspect of the present invention is:

[0014] A wave absorbing material, the raw materials of which include the following components:

[0015] Polyetherimide;

[0016] Conductive fillers;

[0017] Zinc oxide;

[0018] Glycidyl methacrylate.

[0019] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0020] The absorbing material of the present invention has good absorption effect in the 14KHZ-30MHZ frequency band and has better absorption effect in the 30MHz-70GHz frequency band. In addition, it also has the characteristics of high flame retardancy, high temperature resistance, good mechanical properties, etc., and is a very suitable absorbing material for use in electromagnetic darkrooms. The absorbing material of the present invention can break through the pain points of the hard foam absorbing material on the market, which has extremely poor absorption performance below 30MHZ and extremely poor flame retardancy, and is more suitable for harsh environments such as high temperature for high-power electromagnetic wave absorption, and is more cost-effective than any high-power absorbing material (such as honeycomb aramid) currently on the market.

[0021] As a raw material component of the absorbing material, the present invention modifies polyetherimide (PEI) by glycidyl methacrylate (PMAG), so that the absorbing material of the present invention has a lower dielectric constant and dielectric loss. The raw material component is a very excellent substrate for making polymer absorbing materials. The combination with the absorbing additive has a better absorbing effect, and also has excellent mechanical properties and flame retardant properties. PEI is composed of a phenylene ring and an imide bond. The phenylene ring structure has a high polarity and electron cloud density, which enables PEI to effectively absorb electromagnetic wave energy in high frequency bands (such as GHz level); at the same time, the imide bond (C=O-NH-) has the potential for hydrogen bond formation, and can form hydrogen bonds with hydrogen atoms or functional groups with hydrogen in other molecules, thereby enhancing the molecular interaction and stability of the material.

[0022] PMAG contains acrylic acid groups and glycidyl groups. The acrylic acid group (-CH2-CH(CO2H)-) has certain polarity and hydrophilicity, while the glycidyl group (-O-(CH2CH2O)n-) increases the flexibility of the material and the length of the molecular chain, making the material have certain wave absorption performance in the low frequency band (such as kHz level).

[0023] In addition, these functional groups of PEI and PMAG also interact with other molecules through hydrogen bonds, further regulating the dielectric constant and mechanical properties of the material. Specifically, the hydrogen atom (NH) in the imide bond is an excellent hydrogen bond donor, and the formation of hydrogen bonds depends on the electron density distribution and spatial configuration around the NH bond in the PEI molecule; the phenylene ring structure exhibits high hydrogen bond acceptance, especially the C=O bond on it can serve as a hydrogen bond acceptor. These hydrogen bond donors and hydrogen bond acceptors can form hydrogen bond interactions with hydrogen bond acceptors (hydroxyl groups) in the conductive filler molecules.

[0024] The carboxyl group (-COOH) in the acrylic group of PMAG can form hydrogen bonds with the hydrogen atoms in PEI, enhancing the interaction between molecules and forming a PEI-PMAG-conductive filler combination. The complementary properties of this combination work together on the absorbing and mechanical properties of the absorbing material.

[0025] According to one embodiment of the present invention, the raw materials of the absorbing material include the following components in parts by weight:

[0026] Polyetherimide, 50-72 parts;

[0027] Conductive filler, 6-30 parts;

[0028] Metal oxide, 1-10 parts;

[0029] Glycidyl methacrylate, 2-8 parts.

[0030] According to one embodiment of the present invention, the raw materials of the absorbing material include the following components in parts by weight:

[0031] Polyetherimide, 61-71.5 parts;

[0032] Conductive filler, 6-20 parts;

[0033] Metal oxide, 3-7.5 parts;

[0034] Glycidyl methacrylate, 5-7.5 parts.

[0035] According to one embodiment of the present invention, polyetherimide (PEI) also has the following characteristics:

[0036] Light weight: product density is 1.05~1.28g / cm 3 The hollow shell structure is lighter than traditional aramid, non-woven fabrics and other absorbing materials of the same size.

[0037] High temperature resistance: PEI absorbing material has a high melting point and glass transition temperature. It can be used continuously at a temperature of 160-180°C, and the instantaneous use temperature can reach over 200°C.

[0038] Chemical corrosion resistance: PEI absorber material has good corrosion resistance to most organic and inorganic chemical reagents.

[0039] Self-lubrication and wear resistance: PEI absorbing material has excellent self-lubrication and wear resistance, and is suitable for applications that strictly require low friction coefficient and wear resistance.

[0040] Flame retardancy: PEI absorber is a very stable polymer. It can meet the GB8624 B1 flame retardant standard without adding any flame retardant, and the oxygen index is greater than 47%.

[0041] Absorbing performance: PEI absorbing materials can still maintain a good and stable dielectric constant and dielectric loss as well as extremely high dielectric strength under harsh conditions such as high temperature, high pressure, high speed, and high humidity.

[0042] Radiation resistance: PEI absorbing materials have excellent resistance to various radiations, good UV resistance, and can withstand high doses of gamma ray irradiation.

[0043] Dimensional stability: PEI absorbing material has extremely low water absorption and linear thermal expansion coefficient, and the product has excellent dimensional stability in various application environments.

[0044] Mechanical properties: PEI absorbers combine toughness and rigidity, and have excellent mechanical strength and fatigue resistance, even better than some metal and alloy materials.

[0045] Processability: PEI absorbing materials can use micro-foam injection molding technology and have good economic and practicality.

[0046] Hydrolysis resistance: It is not chemically affected by water and high-pressure steam, and can maintain excellent properties even when used continuously in high-temperature and high-pressure water.

[0047] According to one embodiment of the present invention, the conductive filler includes at least one of highly conductive carbon black and superconducting carbon nanotubes.

[0048] According to one embodiment of the present invention, the metal oxide includes zinc oxide. Nano zinc oxide has a strong ability to absorb infrared rays, and a large ratio of absorptivity to thermal melting, and can be used in infrared detectors and infrared sensors. Nano zinc oxide also has the characteristics of light weight, light color, and strong wave absorption ability, and can effectively absorb radar waves and attenuate them, and is applied to new wave-absorbing stealth materials.

[0049] According to one embodiment of the present invention, the components of the absorbing material further include an auxiliary agent, which includes at least one of a silane coupling agent, a dispersant, paraffin wax and polyethylene wax. Among them, paraffin wax increases the softness and ductility of the material; polyethylene wax can improve the water resistance and chemical resistance of the absorbing material.

[0050] Specifically, the technical solution adopted according to the second aspect of the present invention is:

[0051] A method for preparing the absorbing material comprises the following steps:

[0052] Polyetherimide, conductive filler, metal oxide and glycidyl methacrylate are mixed, heated and kneaded to obtain a mixture, and the mixture is mixed with a supercritical fluid and subjected to foaming injection molding to obtain the wave absorbing material.

[0053] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0054] First, the supercritical fluid has low surface tension and high diffusivity, which can effectively dissolve the gas in the polymer. The method of the present invention mixes the supercritical fluid with the mixed material, and then forms tiny, evenly distributed bubbles on the absorbing material through foaming injection molding. This method is more accurate and controllable than traditional physical foaming or chemical foaming.

[0055] The introduction of microscopic bubbles can form multiple conductive networks in the material, which can significantly improve the material's wave absorption performance. Therefore, the presence of tiny bubbles can effectively capture and dissipate the incident electromagnetic wave energy, thereby reducing reflection and propagation, and improving the material's wave absorption efficiency and frequency band coverage.

[0056] In addition, the use of supercritical fluids also helps improve the physical properties of materials. Microscopic bubbles can reduce the density of the material, reduce the overall weight, while improving the mechanical strength and thermal stability, making it more suitable for applications in various harsh environmental conditions.

[0057] According to one embodiment of the present invention, the mixing temperature is 90-120°C.

[0058] According to one embodiment of the present invention, the following steps are also included: after obtaining the mixture, the mixture is melt-dispersed, plasticized, extruded, cooled, pelletized and dried by a twin-screw granulator to obtain particles, and then the particles are mixed with a supercritical fluid.

[0059] According to one embodiment of the present invention, the foaming injection molding comprises the following steps: placing the particles into a silo of a micro-foaming injection molding machine, melting and plasticizing the particles, and then passing a gas generating device to mix a supercritical fluid with the particles to obtain the absorbing material.

[0060] Another aspect of the present invention also relates to the application of the absorbing material in a high-power electromagnetic wave darkroom, including the absorbing material as described in the first embodiment. Since the application adopts all the technical solutions of the absorbing material, it has at least all the beneficial effects brought by the technical solutions of the above embodiments.

[0061] According to one embodiment of the present invention, in order to enhance the absorbing performance of the absorbing material, the shape of the absorbing material is set to a multi-layer wedge hollow shell structure, and different shell wall thicknesses are selected according to the height of the wedges. The shell wall thickness is between 0.5-3mm, and there are mounting holes and heat dissipation holes on the base. Figure 1 It is a front view of the multi-layer wedge hollow shell structure of the wave absorbing material of the present invention. Figure 1 A in the figure is 500mm. Figure 1 B in the figure is 500mm. Figure 1 The C in is 100-750mm. Figure 2 It is a bottom view of the multi-layer wedge hollow shell structure of the wave absorbing material of the present invention.

[0062] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0064] Figure 1 It is a front view of the multi-layer wedge hollow shell structure of the wave absorbing material of the present invention.

[0065] Figure 2 It is a bottom view of the multi-layer wedge hollow shell structure of the wave absorbing material of the present invention. DETAILED DESCRIPTION

[0066] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0067] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the embodiments, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0068] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0069] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0070] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0071] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0072] In the examples and comparative examples, polyetherimide was purchased from Dongguan Dongyan Plastic Raw Materials Co., Ltd.

[0073] In the examples and comparative examples, the foaming grade polyetherimide has a product number of 1000R-BR7095, which was purchased from Dongguan Dongyan Plastic Raw Materials Co., Ltd.

[0074] In the examples and comparative examples, the product number of glycidyl methacrylate is GMA-CAS106-91-2, which was purchased from Jinan Kaichuang Chemical Co., Ltd.

[0075] In the examples and comparative examples, the superconducting carbon nanotubes were purchased from Suzhou Kaifa New Materials Co., Ltd. with the product number of CNTS-006-03.

[0076] In the embodiments and comparative examples, the high conductivity carbon black has a product number of CABOT-vxc72, purchased from Cabot (China) Co., Ltd.

[0077] Example 1

[0078] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0079] Foaming grade polyetherimide, 66 parts;

[0080] Highly conductive carbon black, 18 parts;

[0081] superconducting carbon nanotubes, 2 parts;

[0082] Nano zinc oxide, 5 parts;

[0083] Glycidyl methacrylate, 5 parts;

[0084] Silane coupling agent, 4 parts.

[0085] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0086] S1: Grind the foaming grade polyetherimide into powder, and mix it with high-conductivity carbon black, superconducting carbon nanotubes, nano zinc oxide, silane coupling agent, glycidyl methacrylate, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0087] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0088] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0089] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0090] S5 puts the prepared third particles into the hopper of the micro-foam injection molding machine. The material is pushed into the screw. Through the rotation and heating of the screw, the third particles are fully melted and plasticized. At the same time, supercritical fluid nitrogen is injected into the plastic melt through the gas generating device. During the rotation and shearing of the screw, it is fully mixed and injected into the mold to obtain the above-mentioned absorbing material.

[0091] Example 2

[0092] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0093] Foaming grade polyetherimide, 61 parts;

[0094] Highly conductive carbon black, 18 parts;

[0095] superconducting carbon nanotubes, 2 parts;

[0096] Nano zinc oxide, 7.5 parts;

[0097] Glycidyl methacrylate, 7.5 parts;

[0098] Silane coupling agent, 4 parts.

[0099] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0100] S1: Grind the foaming grade polyetherimide into powder, and mix it with high-conductivity carbon black, superconducting carbon nanotubes, nano zinc oxide, silane coupling agent, glycidyl methacrylate, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0101] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0102] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0103] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0104] S5 puts the prepared third particles into the hopper of the micro-foam injection molding machine. The material is pushed into the screw. Through the rotation and heating of the screw, the third particles are fully melted and plasticized. At the same time, supercritical fluid nitrogen is injected into the plastic melt through the gas generating device. During the rotation and shearing of the screw, it is fully mixed and injected into the mold to obtain the above-mentioned absorbing material.

[0105] Comparative Example 1

[0106] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses unfoamed polyetherimide.

[0107] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0108] Polyetherimide, 71.5 parts;

[0109] Highly conductive carbon black, 18 parts;

[0110] superconducting carbon nanotubes, 2 parts;

[0111] Nano zinc oxide, 3 parts;

[0112] Glycidyl methacrylate, 1.5 parts;

[0113] Silane coupling agent, 4 parts.

[0114] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0115] S1: Grinding polyetherimide into powder, and mixing with high-conductivity carbon black, superconducting carbon nanotubes, nano zinc oxide, silane coupling agent, glycidyl methacrylate, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0116] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0117] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0118] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0119] S5: fully melt and plasticize the prepared third particles, and inject them into a mold to obtain the above-mentioned absorbing material.

[0120] Comparative Example 2

[0121] The difference between Comparative Example 2 and Example 1 is that polyethylene wax is used in Comparative Example 2 to replace the glycidyl methacrylate in Example 1.

[0122] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0123] Foaming grade polyetherimide, 66 parts;

[0124] Highly conductive carbon black, 18 parts;

[0125] superconducting carbon nanotubes, 2 parts;

[0126] Nano zinc oxide, 5 parts;

[0127] Polyethylene wax, 5 parts;

[0128] Silane coupling agent, 4 parts.

[0129] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0130] S1: Grind the foaming grade polyetherimide into powder, and mix it with high-conductivity carbon black, superconducting carbon nanotubes, nano zinc oxide, silane coupling agent, glycidyl methacrylate, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0131] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0132] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0133] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0134] S5 puts the prepared third particles into the hopper of the micro-foam injection molding machine. The material is pushed into the screw. Through the rotation and heating of the screw, the third particles are fully melted and plasticized. At the same time, supercritical fluid nitrogen is injected into the plastic melt through the gas generating device. During the rotation and shearing of the screw, it is fully mixed and injected into the mold to obtain the above-mentioned absorbing material.

[0135] Comparative Example 3

[0136] The differences between Comparative Example 3 and Example 1 include: Comparative Example 3 uses unfoamed polyetherimide, and Comparative Example 3 does not introduce nano zinc oxide.

[0137] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0138] Polyetherimide, 74.5 parts;

[0139] Highly conductive carbon black, 18 parts;

[0140] superconducting carbon nanotubes, 2 parts;

[0141] Glycidyl methacrylate, 1.5 parts;

[0142] Silane coupling agent, 4 parts.

[0143] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0144] S1: Grinding polyetherimide into powder, and mixing with high-conductivity carbon black, superconducting carbon nanotubes, silane coupling agent, glycidyl methacrylate, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0145] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0146] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0147] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0148] S5 melts and plasticizes the prepared third particles, and injects them into a mold to obtain the above-mentioned absorbing material.

[0149] Comparative Example 4

[0150] The difference between Comparative Example 4 and Example 1 is that paraffin is used in Comparative Example 4 instead of glycidyl methacrylate in Example 1.

[0151] A wave absorbing material, the raw materials of the wave absorbing material include the following components in parts by weight:

[0152] Foaming grade polyetherimide, 66 parts;

[0153] Highly conductive carbon black, 18 parts;

[0154] superconducting carbon nanotubes, 2 parts;

[0155] Nano zinc oxide, 5 parts;

[0156] Paraffin wax, 5 parts;

[0157] Silane coupling agent, 4 parts.

[0158] The method for preparing the above-mentioned absorbing material comprises the following steps:

[0159] S1: Grind the foaming grade polyetherimide into powder, and mix it with high-conductivity carbon black, superconducting carbon nanotubes, nano zinc oxide, silane coupling agent, paraffin wax, and silane coupling agent in a heated stirring tank at 90° C. for 8 hours to prepare a first mixed material;

[0160] S2 passes the first mixed material through a twin-screw granulator to obtain first granules through melt dispersion, plasticization, extrusion, cooling and granulation;

[0161] S3 passes the first granules through the twin-screw granulator again, and obtains the second granules after melt dispersion, plasticization, extrusion, cooling and granulation;

[0162] S4: placing the obtained second particles in a drying room and drying them for 24 hours to obtain third particles;

[0163] S5 puts the prepared third particles into the hopper of the micro-foam injection molding machine. The material is pushed into the screw. Through the rotation and heating of the screw, the third particles are fully melted and plasticized. At the same time, supercritical fluid nitrogen is injected into the plastic melt through the gas generating device. During the rotation and shearing of the screw, it is fully mixed and injected into the mold to obtain the above-mentioned absorbing material.

[0164] Performance Test:

[0165] The mechanical properties of the absorbing materials prepared in Examples 1-2 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.

[0166] Table 1

[0167]

[0168] As can be seen from Table 1, Comparative Examples 1-2 add nano zinc oxide relative to Comparative Example 3, so that the tensile strength, fracture strain and impact strength of the absorbing material are increased; Example 1 relative to Comparative Example 1, Example 1 uses foaming grade polyetherimide and adds a supercritical fluid injection process, so that the tensile strength, fracture strain and impact strength of the absorbing material of Example 1 are enhanced; Example 1 relative to Comparative Example 2 adds glycidyl methacrylate, so that the tensile strength, fracture strain and impact strength of the absorbing material of Example 1 are also greatly increased, and the mechanical properties are obviously greatly improved; Example 2 increases the amount of glycidyl methacrylate input relative to Example 1, so that the tensile strength, fracture strain and impact strength of the absorbing material of Example 2 are slightly increased, thereby determining that the number of glycidyl methacrylate added is more suitable at 5-7.5 parts, and the increase in mechanical properties after adding more than 7.5 parts is not significantly prominent.

[0169] The flame retardant properties of the absorbing materials prepared in Examples 1-2 and Comparative Examples 1-3 were tested. The test results are shown in Table 2.

[0170] Table 2

[0171]

[0172]

[0173] It can be seen from Table 2 that the flame retardant properties of the absorbing materials of Examples 1-2 and Comparative Examples 1-3 are not much different, and the flammability (2.0 mm) is HB grade, indicating that the flame retardant and heat resistant properties of the absorbing materials of the present invention mainly depend on the high flame retardant and high temperature resistant properties of PEI itself.

[0174] The absorbing performance of the absorbing materials prepared in Examples 1-2 and Comparative Examples 1-3 was tested. The test results are shown in Table 3.

[0175] Table 3

[0176]

[0177]

[0178] It can be seen from the figure in Table 3 that, compared with Comparative Example 3, Comparative Example 1 adds nano zinc oxide, which makes the absorption rate of Comparative Example 1 significantly higher than that of Comparative Example 3 when the absorption rate is less than 1G; Example 1, relative to Comparative Example 1, adopts foamed polyetherimide and adds a supercritical fluid injection process, so that the absorption rate of the absorbing material of Example 1 at 30MHZ-40GHZ is significantly increased; Example 1, relative to Comparative Example 2, adopts glycidyl methacrylate, which makes the absorbing performance of Example 1 at 30MHZ-40GHZ also significantly increased; Example 2, relative to Example 1, increases the amount of glycidyl methacrylate and nano zinc oxide input, so that the absorbing performance of the absorbing material of Example 2 at 30MHZ-40GHZ is significantly improved.

[0179] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A wave absorbing material, characterized in that: The raw materials of the absorbing material include the following components in parts by weight: Foaming grade polyetherimide, 50-72 parts; Conductive filler, 6-30 parts; Nano zinc oxide, 1-10 parts; Glycidyl methacrylate, 2-8 parts; The method for preparing the absorbing material comprises the following steps: The foaming-grade polyetherimide, conductive filler, nano zinc oxide and glycidyl methacrylate are mixed, heated and kneaded to obtain a mixture, and the mixture is mixed with a supercritical fluid and subjected to foaming injection molding to obtain the wave absorbing material.

2. The absorbing material according to claim 1, characterized in that: The raw materials of the absorbing material include the following components in parts by weight: Foaming grade polyetherimide, 61-71.5 parts; Conductive filler, 6-20 parts; Nano zinc oxide, 3-7.5 parts; Glycidyl methacrylate, 5-7.5 parts.

3. The wave absorbing material according to claim 1, characterized in that: The conductive filler includes at least one of highly conductive carbon black and superconducting carbon nanotubes.

4. The absorbing material according to claim 1, characterized in that: The components of the wave absorbing material also include an auxiliary agent, and the auxiliary agent includes at least one of a silane coupling agent, a dispersant, paraffin wax and polyethylene wax.

5. The wave absorbing material according to claim 1, characterized in that: The method for preparing the absorbing material also includes the following steps: after obtaining the mixture, the mixture is melt-dispersed, plasticized, extruded, cooled, pelletized and dried by a twin-screw granulator to obtain particles, and then the particles are mixed with a supercritical fluid.

6. The wave absorbing material according to claim 5, characterized in that: The foaming injection molding comprises the following steps: placing the particles into a silo of a micro-foaming injection molding machine, melting and plasticizing the particles, and then passing a gas generating device to mix a supercritical fluid with the particles to obtain the wave absorbing material.

7. Use of the absorbing material according to any one of claims 1 to 6 in a high-power electromagnetic wave darkroom.

Citation Information

Patent Citations

  • Wave-absorbing gradient material based on additive manufacturing technology and preparation method thereof

    CN108912670A

  • Carbon nano composite wave-absorbing and heat-insulating epoxy foam material and preparation method thereof

    CN113817210A